Faktor-Faktor Yang Berhubungan Dengan Kejadian Missed Nursing Care Di Ruang Rawat Inap Rumah Sakit Bakti Timah Karimun - Rama Febriandini Putri; Utari Christya Wardhani; Sri Muharni (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Missed care (MNC) is a global health care problem that primarily incorporates elements of optimal nursing care needed by patients that are skipped or delayed by nurses. This research is quantitative research with a cross sectional approach, namely research where data is collected only one observation/measurement. Objective: This research aims to determine the independent variables, namely Work Load, Education Level and Years of Work and the dependent variable, namely missed nursing care. Method: This research was carried out in the inpatient room of Bakti Timah Karimun Hospital. The time for carrying out this research until data processing was carried out in March-April 2023. The respondents in this study were all inpatient nurses at Bakti Timah Karimun Hospital who had met the inclusion criteria, totaling 44 respondents using total sampling techniques. The analysis is Univariate Analysis and Bivariate Analysis with statistical testing using the chi-square test. The data collection process was carried out by researchers using a questionnaire. Results: 17 respondents (38.6%) with missed nursing care in the high category. Vocational education level (D3) 26 respondents (59.1%), working period ≤ 3 years 9 respondents (20.5%) and heavy workload 20 respondents (45.5%). Conclusion: that there is a significant relationship between level of education, length of service and workload with the incidence of missed nursing care in the inpatient ward of Bakti Timah Karimun Hospital.